Kajian Miskonsepsi Kesebangunan dengan Three-Tier Test pada Peserta Didik SMP Mambaus Sholihin 2 - Usniatul, Maulida; Irsyadi, M. Khafid; Sari, Ayu Silvi Lisvian (Papanda, 2026)
Inaccurate or flawed understanding of mathematical concepts remains a challenge in the learning process at the junior high school level. One topic particularly prone to misconceptions is similarity, as it involves spatial reasoning and abstract mathematical relations. This study aims to explore the forms and causes of misconceptions in similarity encountered by seventh-grade students at SMP Mambaus Sholihin 2 in the 2024/2025 academic year. Misconceptions are defined as conceptual understandings that deviate from scientific principles, which may hinder the achievement of comprehensive mathematical competence. The study employed a qualitative descriptive approach with the main instruments being a three-tier diagnostic test and interviews. The three-tier test consists of concept-based questions, the reasoning behind the chosen answers, and the students’ confidence levels in those answers, thereby enabling a more comprehensive identification of misconceptions. Among 36 students, several types of misconceptions were identified, including pure misconceptions, false positives, false negatives, as well as categories of partial understanding and non-understanding. The highest proportion was found in the non-understanding category (28.2%), followed by false positive misconceptions (10.4%) and false negative misconceptions (5.2%). These findings indicate that students’ understanding of similarity remains limited, particularly regarding the relationships between sides and angles in plane figures. Contributing factors to these misconceptions include misinterpretation of concepts, limited comprehension of geometric ratios, and a lack of variety in teachers’ instructional approaches. These results are expected to serve as a strategic reference in designing more adaptive and conceptual learning to minimize similar misconceptions in the future.